2012
DOI: 10.1073/pnas.1206136109
|View full text |Cite
|
Sign up to set email alerts
|

A composite bacteriophage alters colonization by an intestinal commensal bacterium

Abstract: The mammalian intestine is home to a dense community of bacteria and its associated bacteriophage (phage). Virtually nothing is known about how phages impact the establishment and maintenance of resident bacterial communities in the intestine. Here, we examine the phages harbored by Enterococcus faecalis, a commensal of the human intestine. We show that E. faecalis strain V583 produces a composite phage (ϕV1/7) derived from two distinct chromosomally encoded prophage elements. One prophage, prophage 1 (ϕV1), e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
194
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(212 citation statements)
references
References 31 publications
3
194
0
10
Order By: Relevance
“…These situations reflect a phage strain that weakly adheres to the slow grower B 2 , but causes relatively more damage to B 1 . From this result we predict a possible virulentphage variant of the experimentally observed 'suicide bombing' recently found for temperate prophages (Duerkop et al, 2012). In other words, although bacterial strains are under evolutionary pressure to increase their net growth rate Bk À a, a fast grower occasionally can be attacked by a combination of a bacterial strain with slow growth rate and a phage strain that preferentially eliminates the fast grower.…”
Section: Fitness Is Context Dependentmentioning
confidence: 95%
“…These situations reflect a phage strain that weakly adheres to the slow grower B 2 , but causes relatively more damage to B 1 . From this result we predict a possible virulentphage variant of the experimentally observed 'suicide bombing' recently found for temperate prophages (Duerkop et al, 2012). In other words, although bacterial strains are under evolutionary pressure to increase their net growth rate Bk À a, a fast grower occasionally can be attacked by a combination of a bacterial strain with slow growth rate and a phage strain that preferentially eliminates the fast grower.…”
Section: Fitness Is Context Dependentmentioning
confidence: 95%
“…Using a more complex defined microbiota, we also observe a diverse range of viral dynamics: (i) exogenous viruses rising in abundance soon after their introduction (with a corresponding decrease in abundance of their putative bacterial hosts) followed by depletion of these viruses from the community without any obvious trace of genetic resistance or adaptation; (ii) exogenous viruses that survive at undetectable levels for almost a week before increasing their abundances, and in one case, displaying genetic variability over time; and (iii) basal levels of induction of 10 prophages with only one prophage achieving a level that produced detectable alteration in the abundance of its bacterial host. Duerkop et al also showed that prophage induction differed in vitro and in vivo, and how under the appropriate conditions induction could provide a fitness benefit to the bacterial host (27), further highlighting the importance of a temperate lifestyle in the gut, and why prophages are so widely distributed in gut bacterial genomes without necessarily being induced at significant levels. Our findings are also consistent with the previous finding that T7 phages are capable of surviving at undetectable levels for 1 wk in germ-free animals before they rise in abundance after gavage of a bacterial host (26); this capacity to maintain infectivity has potential implications for preventive phage therapy.…”
Section: Nonsimultaneous Detection Of Viruses and Community Rearrangementioning
confidence: 99%
“…Many of the viruses in these communities are bacteriophage (Breitbart et al, 2003;Minot et al, 2011;Willner et al, 2011;Pride et al, 2012a;Minot et al, 2013), likely secondary to the abundance of bacterial cells compared with eukaryote cells in these communities. Viruses likely have a key role in microbial population structures by altering the composition of bacterial communities (Duerkop et al, 2012). The interaction of bacteria and viruses is thought to maintain broad bacterial diversity in the local environment via various ecological models, such as constant-diversity dynamics, periodic selection dynamics and kill-the-winner dynamics (Parada et al, 2008;Rodriguez-Valera et al, 2009;Sandaa et al, 2009;Rodriguez-Brito et al, 2010;Allen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%